Opportunities and Challenges of Isbat Talak in Divorce in Indonesia and Abroad - Novia Sari; Abdul Wahab Naf'an; Paisal Paisal; Pirza Adzkia (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2021)
This article presents a discussion of the legal construction of the isbat divorce in religious courts, because the norm regarding the isbat divorce has not yet existed, but there have been many conditions that demand it and many people have suggested it, including the Indonesian Ulema Council through the fatwa commission. There are two main points to be discussed in this article. First, the construction model of isbat talak in religious courts in Indonesia. Second, the opportunities and challenges of implementing this model for couples who are divorced abroad. This study uses a qualitative approach with data collection techniques in documentation. Sources of data were obtained from documents in the form of the Marriage Law and its derivative rules, the Compilation of Islamic Law in Indonesia, and the results of the ijtima' of the MUI Fatwa Commission throughout Indonesia in 2012. This study shows that the isbat talak is possible to be constructed in the religious justice system as recommended by the MUI in the fatwa. This construction is also possible to apply to couples who divorce abroad by paying attention to other relevant regulations.